Radiotherapy upregulates the expression of membrane-bound negative complement regulator proteins on tumor cells and limits complement-mediated tumor cell lysis - Liang, Yingying; Mai, Lixin; Schneeweiss, Jonathan M.; Lopez Perez, Ramon; Kirschfink, Michael; Huber, Peter E. (Cancers, 2025)
Background/Objectives: Radiotherapy (RT) is a mainstay of clinical cancer therapy that causes broad immune responses. The complement system is a pivotal effector mechanism in the innate immune response, but the impact of RT is less well understood. This study investigates the interaction between RT and the complement system as a possible approach to improve immune responses in cancer treatment. Methods: Human solid cancer (lung, prostate, liver, breast cancer), lymphoma, and leukemia cells were irradiated using X-rays and treated with polyclonal antibodies or anti-CD20 monoclonal antibodies, respectively. Chromium release assay was applied to measure cell lysis after radiation with or without complement-activating antibody treatment. The expression of membrane-bound complement regulatory proteins (mCRPs; CD46, CD55, CD59), which confer resistance against complement activation, CD20 expression, apoptosis, and radiation-induced DNA double-strand breaks (γH2AX), was measured by flow cytometry. The radiosensitivity of tumor cells was assessed by colony-forming assay. Results: We demonstrate that RT profoundly impacts complement function by upregulating the expression of membrane-bound complement regulatory proteins (mCRPs) on tumor cells in a dose- and time-dependent manner. Impaired complement-mediated tumor cell lysis could thus potentially contribute to radio-therapeutic resistance. We also observed RT-induced upregulation of CD20 expression on lymphoma and leukemic cells. Notably, complement activation prior to RT proved more effective in inducing RT-dependent early apoptosis compared to post-irradiation treatment. While complement modulation does not significantly alter RT-induced DNA-damage repair mechanisms or intrinsic radiosensitivity in cancer cells, our results suggest that combining RT with complement-based anti-cancer therapy may enhance complement-dependent cyto-toxicity (CDC) and apoptosis in tumor cells. Conclusions: This study sheds light on the complex interplay between RT and the complement system, offering insights into potential novel combinatorial therapeutic strategies and a potential sequential structure for certain tumor types.
Gesehen am 04.12.2025